CHARACTERIZE PATHOGEN RACES AND RESISTANT GENES ACCORDING TO REACTION ON DIFFERENTIAL VARIETIES UNDER SYRIAN CONDITION - Amor Yahyaui; Ahmed EL-Ahmed; Mayada Kayali (Mesopotamia Journal of Agriculture)
Reaction of tested differential varieties against 27 bunt isolates (15 T .caries and 12 T.leavis), collected in 2007. Four Isolates (A5, A6, A9 and A10) overcome the resistant genes Bt0 and Bt7, and were designated as race T-1. Also, seven Isolates (H11, H12, H13, H14, K20, K21 and K22) defeated the resistant genes Bt0, Bt2 and Bt3, and were designated as race T-11; two other isolates (H15 and Da16) defeated resistant genes Bt7, Bt1 and Bt0, and were called race L-4. Finally, five Isolates (A3, A4, A5, A7 and A8) defeated the resistant genes Bt0, Bt1, Bt2 and Bt3, and were designated as race L-9. As far as the rest of isolates, they were not similar in their interaction with known universal differential varieties, and are therefore considered as new races and were given new codes. Isolates that broke down the resistance genes Bt0, Bt2, Bt3, Bt4, Bt6, Bt7, Bt13, Bt14, Bt15 and Bp, named as races L-13 and T-17; isolates that defeated resistance genes Bt0, Bt7, Bt13, Bt14, Bt15 and Bp, were named races L-14 and T-18, and the isolate that broke down the resistance genes Bt13, Bt14 and Bt15, were named race L-15